(untitled) (SCIENCE TIME JOURNAL, 2026)
This article explores the role of AI-supported and digital tools in developing the automethodological competence of future teachers of English as a Foreign Language (EFL). In the context of rapid digitalization and the integration of artificial intelligence in education, teacher autonomy and methodological self-regulation have become essential competencies. The study analyzes theoretical foundations of automethodological competence, examines modern AI-based digital tools, and highlights their pedagogical potential in pre-service teacher education. The article concludes that the effective integration of AI-supported tools significantly enhances reflective practice, independent decision-making, and professional growth of future EFL teachers.